Consistency and reproducibility of independent feedings using blood from two consecutive days at varying Plasmodium falciparum gametocyte densities based on both direct membrane feeding assay and direct skin feeding assay - Akala, Hoseah Miima; Aponte, John J.; Achola, Millicent Anyango; Juma, Dennis W.; Opot, Benjamin H.; Maisiba, Risper N.; Okoth, Raphael O.; Juma, Jackline A.; Mwakio, Edwin W.; Mwalo, Maurine A.; Oullo, David O.; Abuom, David; et al. (Malaria journal, 2025)
New malaria control tools are needed to prevent the transmission of parasites from the host to the mosquito vector and vice versa. The infectiousness of Plasmodium falciparum gametocytes obtained from individuals to laboratory-reared mosquitoes should be quantified to employ easily applicable assays for evaluating transmission-blocking interventions. This study aimed to establish the relationship between parasite transmission from humans to mosquitoes both within a person and across persons by assessing the variation in the proportion of infected mosquitoes with at least one oocyst (oocyst prevalence) in a direct membrane feeding assay (DMFA) and direct skin landing feeding assay (DSFA) performed at two consecutive time points in the same human subject with P. falciparum gametocytaemia. A total of 400 adults without symptoms of malaria residing in Western Kenya were screened for the presence of P. falciparum gametocytes. Individuals who tested positive had DMFAs and DSFAs on two subsequent days of feeding, baseline and final visit, to compare mosquito infection rates between the two feeds. Blood samples from 42 individuals testing positive for gametocytes underwent mosquito infection assays. Survival rates of mosquitoes after feeding at baseline and final visit were 13.2 and 11.6 days for DMFA and 12.1 and 11.4 days for DSFA, respectively. The mean oocyst prevalence on feeding at baseline and final visit was 6.3% and 2.2% for DMFA and 5.2% and 2.3% for DSFA, respectively. A not significantly lower prevalence was not observed on at final visit (- 0.016% for DMFA, p = 0.795) and -0.025% for DSFA, p = 0.711 compared to feeding at baseline. The correlation of oocyst prevalence between feeding baseline and final visit for both was low (0.3 95%CI (0.15, 0.51). Exploratory analysis suggests a lower probability of infection on the second day, with lower oocyst density. These findings have implications for future studies and limit the utility of before-after designs in testing transmission-blocking interventions. The findings show comparable infection rates in both DMFA and DSFA, which allows use of less invasive membrane assays in future studies. Trial registration NCT04666350.